HOUSEHOLD WASTE MANAGEMENT TO SUPPORT A CLEAN AND HEALTHY ENVIRONMENT - Lirawati Lirawati Tarihoran (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
Waste is discarded or unused materials resulting from human activities, whether at the household, industrial, or mining scales. At certain concentrations, the presence of waste can negatively impact the environment and human health, so proper waste management is necessary. Household waste is waste originating from kitchens, bathrooms, laundry, leftover household industry materials, and human feces. Excessive household waste, if left unattended, has high potential to pollute and poison the environment. Household waste management aims to prevent environmental contamination which could interfere with public health. Method: This paper is a literature study from various sources and references regarding waste. Results: Solid waste originating from household waste includes both organic and inorganic waste. There are three types of waste processing: physical processing, chemical processing, and biological processing. Environmental pollution due to household waste has encompassed all elements including air, water, and soil. Conclusion: Proper household waste processing is essential to prevent environmental contamination. Good household waste management should be tailored to the type of household waste generated.